Low Bone Mineral Density and High Bone Turnover in Patients With Non-Hodgkin's Lymphoma (NHL) Who Receive Frontline Therapy: Results of a Multicenter Prospective Study. Issue 6 (December 2019) - Anargyrou, Konstantinos; Fotiou, Despina; Vassilakopoulos, Theodoros P.; Christoulas, Dimitrios; Makras, Polyzois; Dimou, Maria; Ntanasis-Stathopoulos, Ioannis; Masouridou, Stavroula; Angelopoulou, Maria K.; Papatheodorou, Athanasios; Tsionos, Konstantinos; Panayiotidis, Panayiotis; et al.
Abstract : Abstract: Chemotherapy associated osteoporosis is a severe problem in patients with malignant diseases as it increases the risk for fractures and deteriorates quality of life. There are very limited data in the literature for the effect of chemotherapy on bone metabolism of adult patients with Non-Hodgkin Lymphoma (NHL). We prospectively evaluated bone remodeling pre- and post-chemotherapy in 61 patients with newly diagnosed NHL. First-line chemotherapy resulted in high bone turnover, which led to increased bone loss and reduced bone mineral density (BMD) of lumbar spine (L1-L4) and femur neck (FN). The reduction of L1-L4 and FN BMD post-chemo was more profound in males and in older patients (>55 years). Patients who received 8 cycles of chemotherapy had a greater reduction of L1-L4 and FN BMD as compared to 6 cycles. The administration of chemotherapy also resulted in a dramatic increase of bone resorption markers (CTX and TRACP-5b), bone formation markers, (bALP and Osteocalcin) and of osteoblast regulator Dickkopf-1. During study period, one patient had a pathological fracture in his right FN.